Impact of Psychotropic Medication Effects on Obesity and the Metabolic Syndrome in People With Serious Mental Illness - Mazereel, Victor; Detraux, Johan; Vancampfort, Davy; van Winkel, Ruud; De Hert, Marc (Frontiers in Endocrinology, 2020)
People with serious mental illness (SMI), including schizophrenia, bipolar disorder and major depressive disorder have a higher mortality rate and shortened life expectancy. This is mainly attributable to physical diseases, particularly cardiovascular diseases (CVDs). Important risk factors for CVDs are obesity and other metabolic abnormalities, which are especially prevalent in people with SMI. Several factors contribute to this increased risk, including unhealthy lifestyles and disparities in health care. Psychotropic medication independently further increases this risk. In this review we want to examine the relationship between obesity and other components of the metabolic syndrome and psychotropic medication in people with SMI.